2023
DOI: 10.3390/cancers15164155
|View full text |Cite
|
Sign up to set email alerts
|

Understanding DNA Damage Response and DNA Repair in Multiple Myeloma

Cole Petrilla,
Joshua Galloway,
Ruchi Kudalkar
et al.

Abstract: Multiple myeloma (MM) is a plasma cell malignancy characterized by several genetic abnormalities, including chromosomal translocations, genomic deletions and gains, and point mutations. DNA damage response (DDR) and DNA repair mechanisms are altered in MM to allow for tumor development, progression, and resistance to therapies. Damaged DNA rarely induces an apoptotic response, given the presence of ataxia-telangiectasia mutated (ATM) loss-of-function or mutations, as well as deletions, mutations, or downregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 97 publications
(124 reference statements)
1
1
0
Order By: Relevance
“…Moreover, another study also showed that aluminium phthalocyanine tetra sulfonate (AlPcS 4 )-mediated PDT induced DNA damage in laryngeal cancer ( 35 ). The upregulation of ATM in response to DSB in our study is consistent with established evidence where ATM-mediated repair is believed to be the main mechanism in the DDR pathway to mend DSB lesions ( 33 , 48 ). Furthermore, ATM functions in the regulation of cell cycle checkpoints following cellular stress, especially at the G0/G1, S, and G2/M cell cycle arrest ( 33 , 49 ).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, another study also showed that aluminium phthalocyanine tetra sulfonate (AlPcS 4 )-mediated PDT induced DNA damage in laryngeal cancer ( 35 ). The upregulation of ATM in response to DSB in our study is consistent with established evidence where ATM-mediated repair is believed to be the main mechanism in the DDR pathway to mend DSB lesions ( 33 , 48 ). Furthermore, ATM functions in the regulation of cell cycle checkpoints following cellular stress, especially at the G0/G1, S, and G2/M cell cycle arrest ( 33 , 49 ).…”
Section: Discussionsupporting
confidence: 92%
“…In the clonal evolution of plasma dyscrasia, genetic heterogeneity of selective clones undergoing primary genetic events such as hyperdiploid and chromosomal abnormality results in clonal expansion of plasma cells, which is called gammopathy of undermined significance (MGUS) or smouldering multiple myeloma which are pre-malignant conditions. Secondary genetic events such as MYC rearrangement, TP53 mutation, or DNA repair alteration results in malignant condition (multiple myeloma) (Petrilla, 2023). By studying ITH during lateral growth and downward growth (invasion) of tumour evolution, the hierarchy of ITH was seen as early and late branching subclones along the phylogenetic tree.…”
Section: Genetic and Epigenetic Signature Of Cancer Cells And Their M...mentioning
confidence: 99%
“…Furthermore, the identification of 30 genes directly tied to cancer processes within the top GLRP genes underscores the immediate role these genes play in tumorigenesis and BRCAness-specific pathways. Among these, the inclusion of pivotal genes like TP53 and MYC, integral to cell growth and genomic integrity, indicates their direct contribution to the BRCAness phenotype (Li et al, 2012;Carey et al, 2018;Petrilla et al, 2023). This connection offers insights into tumor behavior, response to treatment, and prognosis, painting a comprehensive picture of the genetic landscape pivotal to BRCAness and its underlying mechanisms.…”
Section: Insights From Top Glrp Genes: Transcription Regulation and C...mentioning
confidence: 99%